Ethnic university youth, organizational processes and advocacy spaces in Monterrey, Mexico - García Álvarez, Luis Fernando (2021)
We consider that ethnic youths in conventional universities, in current migratory territories and in the deployment of the exercise of their profession, are the spaces of incidence where a set of social conditions are articulated that configure particular ethnic youth experiences. We propose an ethnographic look at the ethnic university youths in the Monterrey Metropolitan Area (AMM) to emphasize the positioning of some youth ethnic agents based on certain organizational processes, their protagonism and the proposals that they extend in social spaces in order to install and promote inter-ethnic and intercultural relations.